Higher Order Thinking Skills of Speaking Videos on British Council LearnEnglish Website Based on Revised Bloom's Taxonomy : Higher Order Thinking Skills of Speaking Videos on British Council LearnEnglish Website Based on Revised Bloom's Taxonomy - Anggun Dwi Lestari; Ririn Putri Ananda; Ria Angraini (Teaching English and Language Learning English Journal, 2025)
This study investigates the representation of Higher Order Thinking Skills (HOTS) in speaking videos provided on the British Council’s LearnEnglish website based on the Revised Bloom’s Taxonomy. Speaking skills require not only linguistic competence but also higher-level cognitive processes such as analyzing, evaluating, and creating. Using a qualitative descriptive design with content analysis, this research examined twenty speaking videos across levels A1 to B2. Data were collected through transcript analysis and supported by expert triangulation. The findings reveal that HOTS are embedded at all proficiency levels, with analyzing and evaluating frequently occurring at lower levels, while creating is more dominant at higher levels, particularly B2. These results indicate that LearnEnglish speaking videos promote not only communicative competence but also critical and creative thinking. The study contributes pedagogical insights for teachers, material developers, and learners in integrating HOTS-oriented digital speaking materials.